Soil Methane and Carbon Dioxide Fluxes from Cropland and Riparian Buffers in Different Hydrogeomorphic Settings. Issue 4 (1st July 2015) - Jacinthe, P. A.; Vidon, P.; Fisher, K.; Liu, X.; Baker, M. E.
Abstract : Riparian buffers contribute to the mitigation of nutrient pollution in agricultural landscapes, but there is concern regarding their potential to be hot spots of greenhouse gas production. This study compared soil CO2 and CH4 fluxes in adjacent crop fields and riparian buffers (a flood‐prone forest and a flood‐protected grassland along an incised channel) and examined the impact of water table depth (WTD) and flood events on the variability of gas fluxes in riparian zones. Results showed significantly ( P < 0.001) higher CO2 emission in riparian areas than in adjoining croplands (6.8 ± 0.6 vs. 3.6 ± 0.5 Mg CO2 –C ha −1 yr −1 ; mean ± SE). Daily flux of CO2 and soil temperature were significantly related ( P < 0.002), with Q10 values ranging between 1.75 and 2.53. Significant relationships ( P < 0.05) were found between CH4 daily flux and WTD. Flood events resulted in enhanced CH4 emission (up to +44.5 mg CH4 –C m −2 d −1 in a swale) under warm soil conditions (>22°C), but the effect of flooding was less pronounced in early spring (emission <1.06 mg CH4 –C m −2 d −1 ), probably due to low soil temperature. Although CH4 flux direction alternated at all sites, overall the croplands and the flood‐affected riparian forest were CH4 sources, with annual emission averaging +0.04 ± 0.17 and +0.92 ± 1.6 kg CH4 –C ha −1, respectively. In the riparian forest, a topographic depression (<8% of the total area) accounted for 78% of the annual CH4 emission, underscoring the significance of landscape heterogeneity on CH4 dynamics in riparian buffers. The nonflooded riparian grassland, however, was a net CH4 sink (−1.08 ± 0.22 kg CH4 –C ha −1 yr −1 ), probably due to the presence of subsurface tile drains and a dredged/incised channel at that study site. Although these hydrological alterations may have contributed to improvement in the CH4 sink strength of the riparian grassland, this must be weighed against the water quality maintenance functions and other ecological services provided by riparian buffers.